Professional development for out-of-field post-primary teachers of mathematics: an analysis of the impact of mathematics specific pedagogy training - O'Meara, Niamh; Faulkner, Fiona (Irish educational studies, 2022)
Research shows that teachers influence students' attitudes towards; performance in; and perceptions of a subject. Hence, the need to improve the teaching and learning of many curricular subjects has been well documented for many years. This paper focusses on efforts made to develop competence among out-of-field teachers of mathematics and evaluates the impact of one component of a continuous professional development (CPD) programme on teachers' self-efficacy and self-reported teaching styles. As part of this CPD programme, teachers engaged in a series of subject-specific pedagogy workshops and while classroom observations were not feasible they did complete pre- and post-workshop questionnaires to determine the impact that these workshops had on their mathematics teaching efficacy and their reported approach to teaching, both of which researchers consider to be key to effective teaching. Analysis of the quantitative data showed that the workshops led to statistically significant improvements in mathematics teaching efficacy among participants, while analysis of the qualitative data highlighted a shift from procedural or teacher-led approaches to more student-centred approaches that focussed on developing understanding. As such the programme was deemed to have a positive effect on the effectiveness of these teachers.